STUDI INTERFACE: KEBUTUHAN INFORMASI DALAM PENGEMBANGAN WEBSITE ARSIP DAN INFORMASI ESPORTS INDONESIA - Farqo, Tedi Mursalat; Grahita, Banung (P3M Politeknik Negeri Banjarmasin, 2025)
Indonesia’s esports sector is growing rapidly, yet information needs for esports professional player scouting remain underserved. This study models the information requirements and interface design of an Indonesian esports archive website through media observation and interviews with team managers and coaches. Core needs include periodic tournament statistics, phase-based performance (early, mid, late), and player playstyle. We followed a user-centered design framework (Five Planes) and evaluated the prototype via scenario-based usability testing (n=5). Users completed tasks under target times and rated navigation and statistical visualizations as informative. Improvements focus on last-update indicators, in-page shortcuts, and user help. The study contributes a content model and prioritization of team/player performance attributes for scouting, along with actionable design patterns for a Indonesia esports archive platform.